National standard for stem cell transplantation collection, processing, storage and infusion of haemopoietic stem cell and therapeutic cells (Kementerian Kesihatan Malaysia, 2009)
""The National Standard for Stem Cell Transplantation:Collection, Processing, Storage and Infusion of Haemopoietic Stem Cell and Therapeutic Cells" to serve as a guide to all personnel involved in haemopoietic stem cell transplant to ensure safe and affective procedures are carried out and the viability and quality of the haemopoietic stem cells and therapeutic cells are preserved." -- foreword